Penilaian Rheumatoid Arthritis Terintegrasi Smartphone Sebagai Solusi Teknologi Dalam Meningkatkan Kualitas Pelayanan Keperawatan : Kajian Literatur - Faraniara Faraniara; Roro Tutik Sri Haryati (Citra Delima : Jurnal Ilmiah STIKES Citra Delima Bangka Belitung, 2019)
Patients with chronic conditions such as rheumatoid arthritis need to manage their health to minimize disease activity that often comes unpredictably. Increased stimulation that lasts long can cause irreversible damage to the joints and adversely affects the quality of life. At present, there are many types of cellular applications developed to help patients in managing rheumatoid arthritis. The purpose of this article is to explore the potential for smartphone use in Indonesia, especially in the area of ​​medical-surgical nursing. The literature review of this article was obtained from PubMed, CINAHL, Wiley online library, SAGE and Medline from 2013-2018. Some pilot countries such as the United States, New Zealand, Portugal, and Japan have proven the contribution of smartphones in improving service quality. The use of smartphones in the assessment of rheumatoid arthritis can be applied in Indonesia to see the many benefits that can be obtained. Indonesian nurses should be able to be actively involved in this digital management system. Further research is still very much needed in the development of the assessment of rheumatoid arthritis.